Radio Follow-up Observations of SN 2023ixf by Japanese and Korean Very Long Baseline Interferometers - Yuhei Iwata; Masanori Akimoto; Tomoki Matsuoka; Keiichi Maeda; Yoshinori Yonekura; Nozomu Tominaga; Takashi J. Moriya; Kenta Fujisawa; Kotaro Niinuma; Sung-Chul Yoon; Jae-Joon Lee; Taehyun Jung; et al. (The Astrophysical Journal)
We report on radio follow-up observations of the nearby Type II supernova SN 2023ixf, spanning from 1.7 to 269.9 days after the explosion, conducted using three very long baseline interferometers (VLBIs), which are the Japanese VLBI Network, the VLBI Exploration of Radio Astrometry, and the Korean VLBI Network. In three observation epochs (152.3, 206.1, and 269.9 days), we detected emission at the 6.9 and 8.4 GHz bands, with a flux density of ~5 mJy. The flux density reached a peak at around 206.1 days, which is longer than the timescale to reach the peak observed in typical Type II supernovae. Based on an analytical model of radio emission, our late-time detections were inferred to be due to decreasing optical depth. In this case, the mass-loss rate of the progenitor is estimated to have increased from ~10 ^−6 –10 ^−5 M _⊙ yr ^−1 to ~10 ^−4 M _⊙ yr ^−1 between 28 and 6 yr before the explosion. Our radio constraints are also consistent with the mass-loss rate needed to produce a confined circumstellar medium proposed by previous studies, which suggest that the mass-loss rate increased from ~10 ^−4 M _⊙ yr ^−1 to ≳10 ^−2 M _⊙ yr ^−1 in the last few years before the explosion.